Kritik Hadis “Sayap Lalat adalah Obat” dan Relevansinya dengan Sains Modern - Hakim, Lukman; Azhary, Muhammad Royyan Faqih; bin Asis, Joharis; Firdaus, Ahmad; Hasbillah, Ahmad ‘Ubaydi (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2025)
Hadith, as the second source of Islamic law, plays an important role in the lives of Muslims. However, not all hadiths are of equal standing, making hadith criticism essential. This research aims to analyze the hadith about a fly falling into a drink through the approach of 'Ilal al-Hadith criticism to find potential hidden defects ('illah qadīhah) and to analyze its relevance and meaning in the context of modern science. The research method used is qualitative with a library research approach. Data were analyzed through takhrij al-Hadis, dirasah al-Asanid, analysis al-Matn, and istinbat al-Ma'ani. The results of the study indicate that the sanad of the fly hadith is sahih and no 'illat qadīhah was found. Matan criticism shows the need for contextual interpretation. In the context of modern science, this hadith is relevant to scientific findings in the fields of microbiology and medicine, which indicate that flies carry disease-causing microorganisms but also have self-defense mechanisms that have the potential to produce neutralizing substances. This study concludes that the fly hadith can be understood as a signal about the importance of maintaining a balance between disease and antidote, as well as the hidden potential benefits in seemingly harmful organisms.